Effects of Standardized Ileal Digestible Threonine to Lysine Ratio on Growth Performance of PIC Line 337 × 1050 Pigs - Rafe Q. Royall; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Carine M. Vier; Matthew Spindler; Uislei Orlando; Luis Zaragoza; Ning Lu; Wayne Cast; et al. (Kansas Agricultural Experiment Station Research Reports, 2023)
The objective of this research was to evaluate the impact of varying SID Thr:Lys ratios on growth performance, removals, and mortality rates of late-nursery, grower, and finishing PIC 337 × 1050 pigs. In each experiment, pens of pigs were blocked by BW and randomly assigned to 1 of 5 dietary treatments in a randomized complete block design with 19 to 27 pigs per pen and 8, 7, and 7 replications per treatment in Exp. 1, 2, and 3, respectively. In Exp. 1, 987 pigs (initially 26.0 ± 0.70 lb) were used from 26 to 54 lb. In Exp. 2, 875 pigs (initially 95.5 ± 1.17 lb) were used from 95 to 155 lb. In Exp. 3, 824 pigs (initially 224.4 ± 1.85 lb) were used from 224 to 297 lb. Pens were randomly assigned to 1 of 5 dietary treatments with increasing SID Thr:Lys ratios at 53, 58, 62, 65, and 68% in Exp. 1 and 2, and 56.5, 60, 64, 68, and 72.5% in Exp. 3. Diets were corn-soybean meal-based. Diets with the lowest and highest Thr:Lys ratios were blended to achieve the target SID Thr:Lys treatments in each experiment. Between experiments, all pens of pigs were placed on a common diet for 23 (Exp. 1 and 2) and 32 d (Exp. 2 and 3) to provide opportunity for compensatory growth prior to initiation of the next experiment. In Exp. 1 (26 to 54 lb), ADG and final BW increased linearly (P≤ 0.006) while ADFI, Thr intake/d, and Thr intake/kg of gain increased quadratically (P≤ 0.001). Overall, F/G improved (quadratic,P≤ 0.001) as Thr:Lys ratio increased. Additionally, Lys intake/d increased (quadratic,P<0.001) while Lys intake/ kg of gain decreased (quadratic,P<0.001) with increasing Thr:Lys ratio. The quadratic polynomial (QP) model predicted greater than 68% SID Thr:Lys was required for ADG from 26 to 54 lb, while a QP model suggested that minimum F/G was achieved at 62.1% SID Thr:Lys. In Exp. 2 (95 to 155 lb), ADG, final BW, Thr intake/d, and Thr intake/kg of gain increased (linear,P≤ 0.05) and F/G improved (linear,P= 0.030) as dietary Thr:Lys increased. Moreover, Lys intake/kg of gain decreased (linear,P= 0.023) with increasing Thr:Lys ratio. For model analysis, QP models suggested optimum ADG and F/G were achieved at levels greater than 68% SID Thr:Lys. However, similar fitting broken-line quadratic (BLQ) and broken-line linear (BLL) models predicted no further improvement to F/G and ADG beyond 61 and 67% SID Thr:Lys, respectively. In Exp. 3 (224 to 297 lb), increasing SID Thr:Lys increased (linear,P≤ 0.001) Thr intake/d and Thr intake/kg of gain. In addition, increasing SID Thr:Lys ratios tended (P≤ 0.086) to quadratically increase(P ≤ 0.086) ADFI and BW of pigs at the second marketing event. However, no other response criteria were impacted (P≥ 0.10) by dietary Thr:Lys. Due to a lack of ADG and F/G responses, prediction models were not developed. In summary, these results suggest the optimal SID Thr:Lys level for 26- to 54-lb pigs is 62.1% for feed efficiency and greater than 68% for ADG. From 95 to 155 lb, the requirement was predicted at or above 61 and 67% SID Thr:Lys for F/G and ADG, respectively. However, with the variation in response criteria in Exp. 3 (224 to 297 lb), we were unable to statistically define a requirement estimate.
Keywords: amino acid; grow-finish pig; threonine; nutrition requirement